If a 15 lbs dog eats................................17/8 cups of food
a 34 lbs dog will eat,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,? cups
(34 * 17/8)/15=(34*17)/(15*8)=289/15= 19 4/15 cups of food
That's unusual: repetition: -1/2 - 1/2.
Did you perhaps mean "Factor -1/2 out of (-1/2)x + 6?
Let's do that. Let's rewrite 6 as (-1/2)(-12).
Then (-1/2)x + 6 (-1/2)x -(1/2)(-12)
-------------- = ------------------------ = x - 1/2
-1/2 -1/2
Hope that's what you wanted. If not, please try to apply a similar approach to solving this particular problem.
Answer:
c(3c - 1)
Step-by-step explanation:
3c² - c
Common factor = c
Factored:
c(3c - 1)
-12x^6 - 60x^5-75x^4.......GCF = 3x^4
3x^4(-4x^2 - 20x - 25)
3x^4(-2x - 5)(2x + 5) <==
Answer:
It's y-x= -4
Step-by-step explanation:
I drew the graph and figured out the points. Hope this helps.